2012
DOI: 10.1371/journal.pone.0044119
|View full text |Cite
|
Sign up to set email alerts
|

Non-Listening and Self Centered Leadership – Relationships to Socioeconomic Conditions and Employee Mental Health

Abstract: BackgroundThe way in which leadership is experienced in different socioeconomic strata is of interest per se, as well as how it relates to employee mental health.MethodsThree waves of SLOSH (Swedish Longitudinal Occupational Survey of Health, a questionnaire survey on a sample of the Swedish working population) were used, 2006, 2008 and 2010 (n = 5141). The leadership variables were: “Non-listening leadership” (one question: “Does your manager listen to you?” - four response categories), “Self centered leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 21 publications
4
8
0
1
Order By: Relevance
“…This result confirmed the supervisor support, apart from work related social support, associated with employee` health outcome 26) . The reason of less educated younger worker who dropped out at the second survey which might be due to lower work-related support and the lower social domain QoL was found too.…”
Section: Discussionsupporting
confidence: 71%
“…This result confirmed the supervisor support, apart from work related social support, associated with employee` health outcome 26) . The reason of less educated younger worker who dropped out at the second survey which might be due to lower work-related support and the lower social domain QoL was found too.…”
Section: Discussionsupporting
confidence: 71%
“…In the late 1980s psychological demands and decision authority were assessed with the same questionnaire as in the current study in the working population in Stockholm 6 22. During that period, the correlation between psychological demands and decision authority was 0.16 for men and 0.01 for women.…”
Section: Discussionmentioning
confidence: 90%
“…During the measurement months the percentage of unemployed increased from 6% in 2008 to 8.5% in 2010. Based on the same cohort, as described elsewhere,21 22 Swedish employees reported that their managers listened less to them in 2010 and that there was less cultural activity organised for the employees than in 2008. Accordingly, there was a worsening of working conditions during the study period.…”
Section: Discussionmentioning
confidence: 97%
“…Survey of Health (SLOSH) (Theorell et al, 2012). This nationally representative longitudinal cohort study of work environment and health data is collected with comprehensive paper-and-pencil questionnaires mailed to the participants every second year (Kinsten et al, 2007).…”
Section: Sample and Questionnairementioning
confidence: 99%